Targeting M2 Macrophages Alleviates Airway Inflammation and Remodeling in Asthmatic Mice via miR-378a-3p/GRB2 Pathway - Wang, Qiujie; Hong, Luna; Chen, Ming; Shi, Jiangting; Lin, Xiaoling; Huang, Linjie; Tang, Tiantian; Guo, Yimin; Yuan, Xiaoqing; Jiang, Shanping (Frontiers in Molecular Biosciences, 2021)
Background: Asthma is a complex respiratory disease characterized by airway inflammation and remodeling. MicroRNAs (miRNAs) mediate various cellular processes including macrophage polarization and play an important role in the pathogenesis of asthma. In present study, we aimed to screen miRNA profiling involved in macrophage polarization and investigate its possible functions and mechanisms. Methods: An OVA-sensitized mouse model was established and 2-chloroadenosine (2-CA) was used to interfere with macrophages. The airway inflammation and remodeling were assessed. The identification and function of M2 alveolar macrophages were assessed by flow cytometry, RT-qPCR, arginase activity and co-culture experiment. Microarray screening was used to select miRNAs which were related to macrophage polarization and RNA interference (RNAi) technique was performed to confirm the function of the selected miRNA and its target gene. Results: Alveolar macrophages of asthmatic mice showed significant M2 polarization. 2-CA alleviated airway inflammation and remodeling as well as M2 polarization. In vitro, IL-4-induced M2 macrophages promoted the proliferation of α-SMA-positive cells. And miRNA profiling showed a remarkable increased expression of miR-378a-3p in IL-4 induced M2 macrophages. Dual luciferase reporter assay confirmed growth factor receptor binding protein 2 (GRB2) was a target gene of miR-378a-3p. A miR-378a-3p inhibitor and knockdown of GRB2 repolarized alveolar macrophages from M1 to M2 phenotype. Conclusion: Our findings suggest that miR-378a-3p/GRB2 pathway regulates the polarization of alveolar macrophages which acts as a potential therapeutic target for airway inflammation and remodeling in asthma.